ANALISIS MOTIVASI BELAJAR MATEMATIKA DENGAN VIDEO PEMBELAJARAN KELAS VII SMP PANGERAN ANTASARI - Nur Tri Julia; Rivaldo Siahaan (JURNAL MATHEMATIC PAEDAGOGIC, 2022)
The education system of Indonesian during the pandemic is using an online learning system, where in this learning system many problems occur. Among them, do not have a handphone, do not have internet quota and network, and others. This causes many declines. One of them is the reduction of learning motivation. This research uses a qualitative descriptive method, where the researcher has purpose to describe or explain students' motivation to learn mathematics by using learning video media. The source of data is the seventh grade students of Pangeran Antasari Junior High School. The Data is obtained through filling out a questionnaire to determine the category of students' motivation to learn mathematics with 20 statement items. Measurement of statements by using a Likert scale. The result shows that from 27 students as research samples, 8 students are in the very high category, 16 students are in the high category, and 3 students are in the middle category. In addition, the average of all indicators shows that students' motivation to learn mathematics is included in a good category with an average value of 3,04.Keywords: Learning Motivation, Learning Video Media, Mathematics